PSYCHOLOGICAL FACTORS AND DECISION-MAKING STYLES IN THE TRAINING OF FUTURE MANAGERS: AN EDUCATIONAL-PRACTICAL APPROACH - Акіліна, О.В. (SWorldJournal, 2025)
The article examines managerial activity as a process of decision-making under complex and dynamic conditions, where not only economic and legal aspects but also cognitive, emotional, and socio-psychological factors play a decisive role. In the modern env